China and the United Nations framework convention on climate change: the politics of institutional categorization. (10th June 2016) - Ella, Doron
Abstract: This article examines how categorization mechanisms of the United Nations Framework Convention on Climate Change (UNFCCC) have affected the dynamics between China and other member states during the process of environmental negotiations, and how this categorized institutional environment influenced members' bargaining positions during the studied period. It argues that by categorizing it as a non-Annex I Party, the UNFCCC conferred on China a context-specific role of a developing country and legitimized its reluctance to abide through legally binding commitments. Yet, as China's capabilities changed, its institutional role as a developing country was perceived by other member states as inappropriate. Consequently, various member states, such as the United States and the European Union, expected China to enact the role of a rising power, which meant abiding by legally binding commitments and abandoning its current category group. Furthermore, during these negotiations, both China and other member states utilized the UNFCCC's categorization mechanisms, by emphasizing institutional categorical positioning, in order to enhance their bargaining power. Therefore, this article illustrates how the parties to the Convention were able to reach a successful, binding, and inclusive agreement in Paris.